Personal and socio-economic profile of dairy farmers and Prevailing housing management practices for dairy animals in Navsari district of Gujarat (Indian Journal of Animal Production and Management, 2024)
A study was conducted to study the socio-economic profile and housing management practices for dairy  animals followed by dairy farmers of Navsari district of Gujarat. The study revealed that majority of the  dairy farmers (46.67%) belonged middle to old age group having moderate literacy rate. Majority of the  respondents were in large farmer’s categories (51.11%) and agriculture cum-livestock as their livelihood  (84.44%) and having well developed dairy co-operative sector in their villages. Majority of respondents  (73.33%) provided pucca houses and kept their animals nearby their dwellings (66.67%). About 65.56 per  cent of respondents had pucca floor in an animal shed and thatched roof (51.11%). Provision of manger was  managemental lacunae as half of the respondents (51.11 %) did not provided manger. Mostly respondents  provided leveled flooring (62.22%) along with provision of pucca urinary drainage (63.33%).
Keywords: Socio- economic; Housing; Management practices; Profile